Impact of anemia on clinical profile, treatment patterns and outcomes in heart failure: a retrospective cohort study - W. K., Ho; B. K., Chung; Hwei Sung, Ling; C. Z. F., Chua; A.Z. Y., Koh; K. C., Cheah; S. L., Kwa; J., Namasoo; C. H., Chai; P. W., Ting; M. J., Khaw; J. K. W., Wong; et al. (European Society of Cardiology, 2025)
Background: Heart failure (HF) is a complex clinical syndrome associated with significant morbidity and mortality worldwide. Anemia are common comorbidities in HF patients and associated with poorer functional capacity and worse clinical outcomes. Despite advancements in HF therapies, the coexistence of anemia presents unique challenges in optimizing treatment. Current evidence highlights the need for a better understanding of the baseline characteristics, treatment patterns, and outcomes in HF patients stratified by anemia status. Identifying these differences may provide insights into the pathophysiology of HF and inform strategies for improving outcomes in this vulnerable population. Objective: This study seeks to bridge this knowledge gap by comparing baseline demographics, treatment regimens, and clinical outcomes between HF patients with anemia and those without anaemia. Methods: This retrospective cohort study analyzed 525 HF patients treated across 10 hospitals from January 2021 to June 2023. In this study, anemia is defined using hemoglobin (Hb) thresholds set by the World Health Organization (WHO): men: Hb < 13 g/dL and women: Hb < 12 g/dL. Patients were divided into anemia (n=146, 27.8%) and non-anemia (n=379, 72.2%) groups based on hemoglobin levels. Baseline demographics, comorbidities, medication regimens, New York Heart Association (NYHA) functional class, and Ejection fraction (EF) were compared. GDMT prescription and outcomes, including HF hospitalization, mortality, and a composite endpoint at 6 months, were assessed. Results: Patients with anemia were older (60.7±14.3 vs. 54.5±13.6 years, p<0.001) and more frequently female (52.7% vs. 14%, p<0.001). Comorbidities, including diabetes mellitus (49.3% vs. 37.2%, p=0.009) and chronic kidney disease (41.1% vs. 23.7%, p<0.001), were more prevalent in the anemia group. The use of renin-angiotensin-aldosterone system inhibitors (RAAS) was significantly lower in patients with anemia, even during follow-ups at 3 months (75.4% vs. 88.9%, p<0.001) and 6 months (79.4 % vs. 90.4%, p<0.001). Patients with anemia had worse functional status, with a higher proportion in NYHA Class 3 and 4 prior to the clinic visit (42.4% vs. 24.9%, p=0.012) and at 6 months (9% vs. 2.2%, p=0.007). EF was comparable at baseline between the two groups and improved similarly over time. Clinical outcomes revealed higher HF hospitalization rates in the anemia group at 6 months (13% vs. 5.8%, p=0.006), though mortality (11.1% vs. 6.8%, p=0.112) and composite outcomes (20.5% vs. 14.8%, p=0.109) did not significantly differ. Conclusion: HF patients with anemia exhibit a distinct clinical profile, with higher comorbidity burdens, worse functional status, and poorer treatment prescription over time. These factors contribute to higher HF hospitalization rates and emphasize the need for tailored interventions to address the unique challenges faced by this subgroup.